2013
DOI: 10.1644/900.1
|View full text |Cite
|
Sign up to set email alerts
|

Panthera pardus(Carnivora: Felidae)

Abstract: Panthera pardus (leopard;Linnaeus, 1758) is the smallest of the 4 large felids in the genus Panthera. A solitary and adaptable species, P. pardus is the widest ranging of all wild felids, inhabiting rain forests, mountains, semiarid environments, and suburban areas throughout sub-Saharan Africa, the Middle East, and South Asia to the Russian Far East. Despite this distribution, P. pardus is listed as "Near Threatened" by the International Union for Conservation of Nature and Natural Resources and several Asian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 148 publications
0
67
0
Order By: Relevance
“…It has been previously reported that P. pardus competes for food with P. leo, P. tigris, Crocuta crocuta (Erxleben, 1777), and Lycaon pictus (Temminck, 1820) (Hayward & Kerley, 2008;Stein & Hayssen, 2013). To avoid attacks from potential predators, P. pardus tends to hunt at different times of the day and to avoid areas where potential predators are most abundant (Hayward & Kerley, 2008;Stein & Hayssen, 2013).…”
Section: Discussion Cranial Ontogeny In Panthera Lineagementioning
confidence: 99%
See 3 more Smart Citations
“…It has been previously reported that P. pardus competes for food with P. leo, P. tigris, Crocuta crocuta (Erxleben, 1777), and Lycaon pictus (Temminck, 1820) (Hayward & Kerley, 2008;Stein & Hayssen, 2013). To avoid attacks from potential predators, P. pardus tends to hunt at different times of the day and to avoid areas where potential predators are most abundant (Hayward & Kerley, 2008;Stein & Hayssen, 2013).…”
Section: Discussion Cranial Ontogeny In Panthera Lineagementioning
confidence: 99%
“…The four study species (Panthera leo, P. onca, P. pardus, and P. tigris) have similar gestation periods (88-112 days: Seymour, 1989;Haas et al, 2005;Sunquist & Sunquist, 2009;Stein & Hayssen, 2013) and litter size (1-4 cubs: Maz ak, 1981;Seymour, 1989;Sunquist & Sunquist, 2002;Haas et al, 2005). The smallest weight at birth is that of P. pardus (300-700 g Hemmer, 1979), followed by P. onca (700-900 g, Seymour, 1989), P. leo (1000 g, Hemmer, 1979), and P. tigris (780-1600 g, Maz ak, 1981).…”
Section: Materials and Methods Background Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Their ubiquitous and eurythermal nature and their opportunistic behaviour allow them to adapt well to different biotopes. Nowadays, different subspecies are distributed throughout different areas of Africa and Asia (Turner and Ant on, 1997;Bertram, 1999;Hayward et al, 2006;Macdonald et al, 2010;Stein and Hayssen, 2013).…”
Section: Introductionmentioning
confidence: 99%